Edukasi Dan Literasi Keuangan Rumah Tangga Untuk Meminimalisir Peran Pinjol Di Era New Normal Di Kelurahan Bunulrejo, Kecamatan Blimbing Kota Malang - Yenny Kornitasari (CV. Multi Kreasi Media, 2023)
The goal to be achieved in this Abdhi Dharma service is to implement the financial literacy movement for economically vulnerable people; provide an understanding of the importance of financial management to the public through assistance in managing simple financial records; Knowing effective methods to minimize people's habits to borrow money from loan sharks both offline and online with creative and productive assistance. Partners in this community service activity are PKK mothers, the majority of whom are housewives with PKK coordinator-based problems, namely the low source of income for the head of the family, financial management skills and low financial literacy, which are very vulnerable to getting income quickly through loans (online loans). ) which is illegal because of its convenience. The reason for choosing this service partner was PKK mothers, because based on information from partners, most of the PKK members had been caught in illegal loans. The results of this dedication knowledge after the program was held, our PKK partners regarding financial literacy and online credit have increased and have the potential to increase income due to a significant increase in creative entrepreneurship knowledge. With this program, partners can become more productive so that they can increase the income of the head of the family